Sharia issues in halal slaughterhouses and abattoirs: problems and solutions - Alabi Lateef Zikrullah
Halal food generally and the meat industry especially have become a big industry around the world. Since the industrialization of meat and poultry production, producers tend to speed up the production in order to meet the demand of the market. Slaughtering procedures with modem technology have been introduced in major Halal slaughterhouses and abattoirs around the world and even Muslim countries like Malaysia. Electro-narcosis of different types was introduced with the aim of rendering the animal unconscious and to reduce the pain to facilitate the slaughtering process. Islamic institutions and Halal regulatory bodies, likewise scholars and jurists are found to be inconsistent with regard to the legality of these modem techniques. This study is aimed to bring the attention of the readers to the awareness regarding the sharia rulings and the principles for animal meat production. Due to increasing demand for halal meat and poultry, there is need to evaluate the common Islamic supervision methodology of Halal slaughterhouses and abattoirs, the reasons for violations of Sharia rulings and a possible means of setting a harmony within the industry that may enhance Halal slaughtering procedures and its genuine certification. A qualitative semi-structured method is employed which resulted in a considerable necessity for the need of assessment of the Sharia rulings improvement in the industry. Differences of opinion would remain a challenge in Islamic communities and among the Sharia experts, thus setting a positive reciprocal measure in our decision may strengthen the Halal industry and upgrade regulatory system.